2020
DOI: 10.4317/jced.57282
|View full text |Cite
|
Sign up to set email alerts
|

Halitosis, reduced salivary flow and the quality of life in pre-kidney transplantation patients

Abstract: Background Halitosis is a condition that affects 50% of adults and one third of patients with chronic kidney disease. The aim of this study was to evaluate oral manifestations and volatile sulfur compounds (VSCs) associated with halitosis and quality of life in pre-kidney transplantation candidates. Material and Methods The organoleptic test (OT) and halimetry (HA) (before and after cysteine mouthwash) were performed in patients with the Oralchroma® device, stimulated (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
1
6
1
1
Order By: Relevance
“…Several studies have shown a direct correlation between the serum accumulation of urea, and other uremic toxins, with the present of ammonia in CKD patients' exhalation [37]. The ammonia accumulation in the oral cavity is responsible for the reduction in salivary flow and for the mouth dry, phenomena usually observed in ESRD patients [36]. Furthermore, this condition leads to the perception of a metallic and unpleasant taste following the ingestion of food, which induces the patient to reduce caloric and protein intake, contributing to the development of protein-energy wasting (PEW) syndrome, typical of CKD patients [38].…”
Section: Saliva and Exhaled Alterationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown a direct correlation between the serum accumulation of urea, and other uremic toxins, with the present of ammonia in CKD patients' exhalation [37]. The ammonia accumulation in the oral cavity is responsible for the reduction in salivary flow and for the mouth dry, phenomena usually observed in ESRD patients [36]. Furthermore, this condition leads to the perception of a metallic and unpleasant taste following the ingestion of food, which induces the patient to reduce caloric and protein intake, contributing to the development of protein-energy wasting (PEW) syndrome, typical of CKD patients [38].…”
Section: Saliva and Exhaled Alterationmentioning
confidence: 99%
“…Nearly one third of end stage renal disease (ESRD) patients show a condition known as uremic halitosis [36]. In fact, the loss of renal function, especially in more advanced CKD stages, induces urea accumulation both in saliva and serum.…”
Section: Saliva and Exhaled Alterationmentioning
confidence: 99%
“…The cross‐sectional studies (HajiFattahi et al, 2015; Han et al, 2014; Herman et al, 2018; Komori et al, 2016; Nazir et al, 2017; Rani et al, 2016; Romano et al, 2020; Santaella et al, 2020; Sikorska‐Żuk & Bochnia, 2018; Suzuki et al, 2016; Takeuchi et al, 2017) exhibited several intra‐oral and extra‐oral factors associated with the systemic diseases for halitosis. Most of the factors are intra‐oral.…”
Section: Resultsmentioning
confidence: 99%
“…These feelings were more likely to be especially present among individuals with a strong belief that others were noticing their breath odor [3]. The assessment of the impact of intra-oral health on QOL by Santaella et al [45] showed a negative influence of halitosis on social disability and psychological discomfort. According to Troger et al [46], halitosis may cause embarrassment, depression and make relationships more difficult.…”
Section: Discussionmentioning
confidence: 99%